2020
DOI: 10.1242/jeb.230870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early-life exposure to sublethal levels of a common neonicotinoid insecticide on the orientation and migration of monarch butterflies (Danaus plexippus)

Abstract: Migratory insects use a variety of innate mechanisms to determine their orientation and maintain correct bearing. For long-distance migrants, such as the monarch butterfly (Danaus plexippus), these journeys could be affected by exposure to environmental contaminants. Neonicotinoids are synthetic insecticides that work by affecting the nervous system of insects, resulting in impairment of their mobility, cognitive performance, and other physiological and behavioural functions. To examine how neonicotinoids migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…Furthermore, our results concerning monarch flight ability also indicated that neonicotinoids might be less relevant to monarch migration than previously suspected, e.g., [40,69]. This conclusion was in agreement with recent findings from field-tracked monarchs that had been exposed to neonicotinoids [29]. Therefore, it is becoming clear that neonicotinoid exposure at concentrations typically found in milkweed does not hinder monarch flight and by extension, migration success.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our results concerning monarch flight ability also indicated that neonicotinoids might be less relevant to monarch migration than previously suspected, e.g., [40,69]. This conclusion was in agreement with recent findings from field-tracked monarchs that had been exposed to neonicotinoids [29]. Therefore, it is becoming clear that neonicotinoid exposure at concentrations typically found in milkweed does not hinder monarch flight and by extension, migration success.…”
Section: Discussionsupporting
confidence: 92%
“…While some evidence has suggested these declines stem from issues related to habitat loss during summer [20][21][22], other research points to problems faced during the fall migration [23][24][25][26]. In particular, neonicotinoids have been suggested as a potential cause of decreased monarch migration success [27][28][29]. Some studies cited the increasing use of neonicotinoids as a correlational factor with declines in eastern monarchs [28,30], and another found that western monarch declines were greater where pesticide use and habitat loss were higher [31].…”
Section: Introductionmentioning
confidence: 99%
“…distilled water) with 4 plants per 1.68 L (6 square inch) pot in environmental chambers at the University of Guelph Phytotron. However, we found no evidence of any measurable effect of neonicotinoid exposure on orientation for monarchs with early-life (caterpillar) exposure to clothianidin compared to controls, either when they were tested in a flight simulator or radio tracked in the wild ( Wilcox et al, 2021 ).…”
Section: Methodscontrasting
confidence: 65%
“…This study was part of a larger project testing the effect of exposure to the neonicotinoid insecticide clothianidin on orientation of fall migratory monarch butterflies ( Wilcox et al, 2021 ). Swamp milkweed ( Asclepias incarnata ) was grown in commercial soil (LA4 Sunshine Loosefill, Sungro Horticulture, MA, USA) treated with either at 4, 8, 15 or 25 ng/g of clothianidin (neonicotinoid insecticide) or a control (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In insects, this has been chiefly studied in managed bees Apis mellifera (Linnaeus, 1758) [ 187 ]. Nonetheless, there is also a growing body of evidence demonstrating adverse consequences on other managed as well as native insects [ 209 , 210 , 211 ].…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%